Anthracophyllum sontraense (Omphalotaceae, Agaricales), A New Species from Danang, Vietnam - Trung Thanh Nguyen; Hanh Hong Do; Toan Nguyen-Sy; Uyen Thi Diem Huynh; Nguyen Thi Lam Hai; Thi Thanh Tam Phan; Thi Thu Hoai Nguyen; Do Tan Khang; Phu Thi Tran (Mycobiology)
During the collection of macrofungi resources in Son Tra Nature Reserve, Danang, Vietnam, two fungal specimens of the genus Anthracophyllum, designated as M34295 and M3457, living on dead still-attached branches of Mussaenda frondosa L. at an elevation around 360 m above the sea level were recorded. The morphological characteristics of the specimens shared some common characteristics with Anthracophyllum spp. However, the specimens possessed some distinct characteristics from other Anthracophylllum species. The phylogenetic analyses based on the combined internal transcribed spacer (ITS) and Large Subunit (LSU) molecular markers of ribosomal RNA genes revealed that the two specimens clustered in a single clade at species level with all tested Anthracophyllum species with strong bootstrap support of 99%. Among Anthracophyllum genus, our specimens seemed closest to A. archeri in morphological and genetic characteristics. Based on the combination of morphological approaches and multilocus phylogenetic analyses, we introduced Anthracophyllum sontraense sp. nov. as a new species. A. sontraense was characterized by its skewed bell-like basidiome with the color of dark blue to midnight blue, 1.0 − 1.5 cm diam, stipeless, light pink lamellae, sparse, occasionally branching. Basidiospores broadly ovoid to subglobose, 6–7 × 5.5–6 µm. To our knowledge, this is the first record of Anthracophyllum fungus in Vietnam.